The Effect of Unionization on Wages: Some Canadian Evidence - Evans, Martin; Ondrack, Daniel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
Recently in the United States there has been a reawakening of interest in the wage effect of unionization (Freeman and Medoff, 1984). The question asked is what is the impact of unionization on overall pay levels and on the wage differentials within the work force? Although there has been considerable research on this issue in the United States (see Lewis, 1984 for a review), there is very little pertinent Canadian analysis (Gunderson, 1980).